Managing people in entrepreneurial organizations learning from the merger of entrepreneurship and human resource management - Katz, Jerome A.; Welbourne, Theresa M. (Advances in entrepreneurship, firm emergence and growth ;, 2002)
The last years of the 20th Century may well have reflected a brief golden age for human resource management. In an economy where ideas and capital were plentiful, the critical facet for success increasingly became human resources. Having the people on hand, with the right skills to bring new products into existence with a first mover advantage became the definitive factor. As a result, policies and initiatives at the intersection of entrepreneurship and human resource management proliferated in an unprecedented way, and is the focus of this volume. As is traditional for this series, the volume includes two major reviews: of HRM in entrepreneurship and of stock related rewards. The volume also includes papers on topics emerging from the retrospective of the dot-com boom and bust, such as optimal methods of recruitment for smaller firms, defining and assessing the new concept of person-entrepreneurship fit, and the impact of union relationships on small high-performance firms.